EXPLORING CHARACTERISTICS OF VACCINATED DOGS THAT FAIL TO ACHIEVE AN ADEQUATE LEVEL OF RABIES VIRUS NEUTRALIZING ANTIBODIES - Anna, Pees M. (My University, 2016)
This study provides additional findings that could potentially have implications for current and future guidelines as they pertain to pet travel, vaccination campaigns, and exposure recommendations. Furthermore, the study provides insight into additional research needed within the area of rabies serology specifically as it pertains to the influence of breed or dog size, primary versus anamnestic responses to vaccination, and smaller sampling intervals to determine the initial detection of immunocompetence.
Keywords: Rabies; Antibodies; Dogs